Investigating The Use of Collaborative Strategic Reading (CSR) in Students' Literacy Activities in A Senior High School (RETAIN, 2023)
The objectives of this study were to investigate the use of Collaborative Strategic Reading included Preview strategy, Click and Clunk strategy, Get the gist strategy, and Wrap up strategy in literacy activities conducted in a senior high school in Surabaya. This study used qualitative design to convey the result and discussion in descriptive manner by using field notes, questionnaires, and interview transcripts as the instruments. The data were collected through non-participant observations, questionnairesdistribution, and interviews. Then, the researcher analyzed the data by familiarizing and organizing, coding and reducing, and interpreting and representing. The result of this study shows that the students use and apply reading strategies of Collaborative Strategic Reading (CSR) during literacy activities. The students apply preview strategy by brainstorming and predicting; click and clunk strategy by monitoring and guessing meaning; get the gist strategy by identifying main idea; and wrap up strategy by formulatingown questions and discussing. Those reading strategies revealed positive impacts on reading comprehension that is followed by critical thinking skill. This research can be used as a reflection and references for some students, practitioners, and further researchers to conduct further studies about Collaborative Strategic Reading.Keywords: Literacy, Reading comprehension, Reading Strategy, and Collaborative Strategic Reading.